Reducing intentions to resist future change: Combined effects of commitment-based HR practices and ethical leadership - Neves, P.; Almeida, P.; Velez, M. J. (Human Resource Management, 2018)
Change management, and particularly the human side of change, is a central tenet of the strategy of contemporary organizations. However, there is little evidence concerning how strategic HR practices influence how individuals anticipate and react to the implementation of a major change and how direct supervisors influence that process. With a sample of 191 employees from multiple organizations, who completed two surveys with a four-week lag, we examined the role of commitment-based HR practices on employees’ intentions to resist future change. We found that commitment-based HR practices contribute to a decrease in intentions to resist future change, measured four weeks later, via increased affective commitment to change. Moreover, we found that this relationship is conditional on ethical leadership, in that it is significant when ethical leadership is high but not when it is low. Building on social exchange and uncertainty reduction theories, our findings contribute to the literature by examining how and under what boundary conditions HR practices are an effective means for organizations to anticipate and manage change.